Last things - West, Jacqueline, 1979- (Greenwillow Books, an imprint of HarperCollinsPublishers, 2019)
"Anders Thorson, front man of his metal band, Last Things, is unusually gifted for a teenager, but strange things in the Minnesota woods near his hometown are threatening him. Thea, the new girl in town, says she's there to protect him, but is that the whole truth?"--